STRESS BEHAVIOUR AMONG POLICE OFFICERS UNDER HUMAN RESOURCES MANAGEMENT (International Journal of Food and Nutritional Sciences, 2022)
Stress damages human beings and it damages their agencies. It could be all pervasive. It may have an effect on people in all occupations and of every age irrespective of intercourse, nationality, academic historical past or function. Pressure is an inevitable part of police employees. Constant and unmanaged strain probably reduces the effectiveness and efficiency of the employees.